ANALYSIS OF THE ETHICAL EFFECT OF LEADERSHIP ON EMPLOYEE PERFORMANCE AND MODERATED WITH EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Antony Sentoso; Fendi Sang Putra (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine the relationship of ethical leadership to employee performance and mediated by employee engagement and organizational citizenship behavior in a tax consultant office in Batam. Employee performance is the dependent variable studied in this study. Ethical leadership as an independent variable was used in this study. Employee engagement and organizational citizenship behavior as variables that mediate the relationship between ethical leadership and employee performance. The sample used in this study are employees who work in companies engaged in tax consulting in Batam. Sources of data used are primary data obtained through questionnaires distributed by examining the influence between variables with panel regression testing method. Ethical leadership directly has a significant and positive influence on employee performance. Ethical leadership directly has a significant and positive effect on employee engagement. Ethical leadership directly has a significant and positive effect on organizational citizenship behavior. Employee engagement directly has a significant and positive effect on employee performance. Organizational citizenship behavior directly has a significant and positive effect on employee performance. Ethical leadership mediated by employee engagement has a significant positive effect on employee performance. Ethical leadership mediated by organizational citizenship behavior has a significant positive effect on employee performance.